GAYA HIDUP MASYARAKAT LOKAL SESUDAH HADIRNYA CAI ASEM (CAS) WATER PARK - Rani Muhardiana (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2023)
The title of research is “Lifestyle on Local Community After the Present Cai Asem (CAS) Water Park”. The background of the research because of the social interaction between local communities and tourist to lead changes in the pattern or the values of community life. Aripin (2005:2) in Manahati Zebua (2016: 316). The sources of Lifestyle from Wheels and Tiger (1971: 27-35) in Solomon “Consumer Behavior” (2011:264) and in Wayan Weda Asmara Dewi (2022: 93). Purpose of this research is to know the lifestyle on local community. Determine whether or not changes or diffeences before and after the presence of Cai Asem (CAS) Water Park. The research has four variable, the first variable is (X1) “ Activities Variable” with Work Indicator (X1.1), Social Event Indicator (X1.2), Entertainment Indicator (X1.3). The second variable or (X2) “Interest Variable” with Home Indicator (X2.1), Fashion Indicator (X2.2), Food Indicator (X2.3). Third variable is (X3) “Opinions Variable” with Business Indicator (X3.1), Education Indicator (X3.2), Culture Indicator (X3.3). The last variable (X4) ‘’Demographics Variable” with Income Indicator (X4.1), Occupation Indicator (X4.2), Stage in Life Cycle Indicator (X4.3). Methods of research is descriptive and t-test, te scale of research is Interval and Accidental Sampling with screening process. Sources of data primer and secunder. The processing data use SPSS 16.0 program. To the biggest and changes in Demographics variables on Income Indicator, and the smallest changes in Opinions Variable on Culture Indicator. Overall the local community have a significant changes. For the next research please other dimention lifestyle.